Mouse Models of Polyglutamine Diseases in Therapeutic Approaches: Review and Data Table. Part II - Switonski, Pawel M. (Humana Press Inc, 2012)
Mouse models of human diseases are created both to understand the pathogenesis of the disorders and to find successful therapies for them. This work is the second part in a series of reviews of mouse models of polyglutamine (polyQ) hereditary disorders and focuses on in vivo experimental therapeutic approaches. Like part I of the polyQ mouse model review, this work is supplemented with a table that contains data from experimental studies of therapeutic approaches in polyQ mouse models. The aim of this review was to characterize the benefits and outcomes of various therapeutic strategies in mouse models. We examine whether the therapeutic strategies are specific to a single disease or are applicable to more than one polyQ disorder in mouse models. In addition, we discuss the suitability of mouse models in therapeutic approaches. Although the majority of therapeutic studies were performed in mouse models of Huntington disease, similar strategies were also used in other disease models. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12035-012-8316-3) contains supplementary material, which is available to authorized users.